Dysfunctional Implantable Loop Recorder Post‐Electrical Cardioversion: A Report of Two Cases - Wael Zaher; Lorenzo Marcon; Antonio Sorgente (Clinical Case Reports)
ABSTRACT We report two occurrences of implantable loop recorder (ILR) dysfunction following electrical cardioversion, likely due to anterior–posterior patch positioning. Close proximity to the electrical field may affect ILRs, emphasizing the need for careful patch placement, similar to other cardiovascular implantable electronic devices.